2017
DOI: 10.1080/10245332.2017.1385194
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of REGγ inhibits the proliferation and migration and promotes the apoptosis of multiple myeloma cells by downregulating NF-κB signal pathway

Abstract: Knockdown of REGγ may inhibit the proliferation and migration, and promote the apoptosis of RPMI-8226 cells possibly by downregulating NF-κB signal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The starting material, 2-chloro-1-methyl-1H-benzimidazole (1) as the starting material, was reacted with hydrazine hydrate to obtain intermediate 2, which was then reacted with 5-bromo-2-hydroxy-1,3 benzenedicarboxaldehyde (4). The reaction produced the target product (5). The NMR spectra of AE-848 are shown in Supplementary Figure 1.…”
Section: Results Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The starting material, 2-chloro-1-methyl-1H-benzimidazole (1) as the starting material, was reacted with hydrazine hydrate to obtain intermediate 2, which was then reacted with 5-bromo-2-hydroxy-1,3 benzenedicarboxaldehyde (4). The reaction produced the target product (5). The NMR spectra of AE-848 are shown in Supplementary Figure 1.…”
Section: Results Chemistrymentioning
confidence: 99%
“…Hyperactivated NF-κB signaling thus serves as an important prognostic biomarker and therapeutic target for MM. 4,5 The PI3K/Akt/mTOR signaling pathway controls a number of biological processes critical to tumorigenesis, including apoptosis, transcription, translation, and cell cycle. 6 A growing number of studies have shown that inhibition of the PI3K/Akt/mTOR signaling pathway triggers apoptosis in MM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our data also demonstrated that PDTC treatment significantly inhibited the USP15-mediated expression of NF-κB-regulated gene products in MM cells. Inhibition of NF-κBp65 expression in MM cells significantly reduced proliferation and apoptosis and decreased Bcl-2 and Bcl-xL expression 28 , 29 . NF-κB inactivation decreases Bcl-2, Bcl-xL and Survivin expression and subsequently activates Caspase-3, which results in MM cell apoptosis 30 , 31 .…”
Section: Discussionmentioning
confidence: 96%
“…In the past decades, researchers have aimed at elucidating the mechanisms regulating the malignant behaviour of MM and identifying key genes contributing to cancer progression. A previous study revealed that knockdown of REGγ inhibits the proliferation and migration, but promotes the apoptosis of MM cells, suggesting that REGγ may serve as a therapeutic target for MM . Additionally, cullin 4A is considered as a marker and promising therapeutic target in MM.…”
Section: Discussionmentioning
confidence: 99%